"Under the Blood" at Azusa Street: Exodus Typology at the Heart of Pentecostal Origins. (12th August 2014) - Pugh, Ben
<x xml:space="preserve">Abstract</x> This article intends to analyse the spirituality of the Azusa Street Mission with a view to achieving two things. Firstly, I will draw attention to an emphasis that seems almost wholly ignored in studies of early Pentecostalism: the blood of Jesus. Secondly, while drawing attention to the considerable prominence of this Christological‐soteriological motif within the discourse of Azusa Street, I will seek to find a context for it that might help to explain it. This context will be explored in biblical, spiritual, and racial terms.